Self-assembly of Silver Nanoparticles and Multiwall Carbon Nanotubes on Decomposed GaAs Surfaces - Unnikrishnan NV; Bartringer J; Mesli A; Al-Harthi SH; Revathy KP; Gard F; George AK; Mamor M (Nanoscale Research Letters, 2010)
Abstract Atomic Force Microscopy complemented by Photoluminescence and Reflection High Energy Electron Diffraction has been used to study self-assembly of silver nanoparticles and multiwall carbon nanotubes on thermally decomposed GaAs (100) surfaces. It has been shown that the decomposition leads to the formation of arsenic plate-like structures. Multiwall carbon nanotubes spin coated on the decomposed surfaces were mostly found to occupy the depressions between the plates and formed boundaries. While direct casting of silver nanoparticles is found to induce microdroplets. Annealing at 300°C was observed to contract the microdroplets into combined structures consisting of silver spots surrounded by silver rings. Moreover, casting of colloidal suspension consists of multiwall carbon nanotubes and silver nanoparticles is observed to cause the formation of 2D compact islands. Depending on the multiwall carbon nanotubes diameter, GaAs/multiwall carbon nanotubes/silver system exhibited photoluminescence with varying strength. Such assembly provides a possible bottom up facile way of roughness controlled fabrication of plasmonic systems on GaAs surfaces.